An Analysis of Teacher Questioning Strategies in Online ESP Classroom Activity - Yulia Indrawati; Rina Herlina; R. Bunga Febriani (Jadila: Journal of Development and Innovation in Language and Literature Education, 2024)
This research aimed to determine the questioning strategies that the English teacher used and the students’ perception of teacher questioning using Zoom meetings in ESP class at the Accounting Education Program. This research applied a descriptive qualitative method. The data were collected from the observation by video recorder during Zoom meetings, interview by audio recorder, and questionnaire. The data was taken from ESP teacher at the Accounting Education Program Universitas Galuh to find out the type of questioning strategies used and the students’ perception of teacher questioning during Zoom meetings. The teacher of the ESP class in the Accounting Education program used all types of questions. Procedural, convergent, and divergent questions are the questions used by the teacher in online classroom interaction. Students’ perception of teacher questioning in ESP class, 60% of students’ agreeing to the teacher question through Zoom meetings makes online learning more interactive, 53.3% of students’ agreeing to the teacher questioning helped improve their speaking skills in online classroom activity, 53.3% students’ agreeing to the teacher questioning helped them increased their confidence, 46.7% students choose neutral that interaction in the zoom meeting is understandable and the last 46.% students choose neutral that interaction in the Zoom meetings is very clear. The English teacher must be aware of using types of questions that will be asked to the students.